Developing & Deploying Algorithms for Information Extraction using Classification Measures for Named Entity Recognition - Khan, Rehan; Singh, A.J (International Journal of Computer Sciences and Engineering, 2025)
The web is full of the content which is either in complete or semi unstructured form and retrieving the essential data out of this unstructured form is very difficult so the concept of the information extraction (IE) keeping in view the necessary parameters becomes highly essential. This paper presents a comparative study for how the problem of information extraction can be handled for a dataset by taking the first step towards IE of named entity recognition (NER) into consideration. Various classifiers/techniques and impact of pipeline on some of them is discussed in this paper for NER and based on the results with keeping the due response time into consideration the classifier/technique of conditional random fields for NER serves out to be the best with an average recall and precision of 0.97 each helping in predicting efficiently of whether a given word is a part of the named entity or not. The automation in the field of medical science for search of the patient for clinical trials from the clinical databases serves to be the most important area of concern at the present time & this paper provides an approach for choosing the technique according to parameters, also discussing the results of the novel algorithmic approach